Kinerja Guru dalam Menyiapkan dan Menyusun Rencana Pelaksanaan Pembelajaran (RPP) - Sri Andriani; Saleh Hidayat; Indawan Indawan (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to describe teachers' performance in compiling and preparing lesson plans. This research method is carried out with a qualitative approach with a descriptive design. The sample in this study amounted to 15 high school biology teachers in OKU Regency. Data collection methods are done using observation sheets, interviews, and documentation. The results showed that: 1) the behavior of teachers in preparing and compiling lesson plans was largely independent, only relying on lesson plans obtained from other parties such as downloads from the internet, then the lesson plans that were used as references were copied or adopted only; 2) teachers have good knowledge of lesson plans and the steps for their preparation, and teachers prepare lesson plans at the beginning of each semester which is submitted to the school; 3) the quality of the lesson plans prepared by the teacher directly has an average value of 5. In conclusion, the teacher's quality of the lesson plans is still in the poor category. Keywords: Teacher, Performance, Lesson Plans